SIFAT FISIK TANAH DAN PERTUMBUHAN TANAMAN PADI (Oryza sativa L.) SEBAGAI DAMPAK PENGAPLIKASIAN DEKOMPOSER PADA SISTEM REKOMENDASI PEMUPUKAN BERBASIS CITRA KAMERA MULTISPEKTRAL DI SUKAMANDIJAYA, JAWA BARAT - Rizki Puspita Rahmawati; Sugeng Prijono; Syawaluddin Akbar; Yazid Abdur Rahman (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Application of balanced fertilizers and the use of decomposers on land can improve soil health and nutrient availability for plants. Giving recommended doses of fertilization through the use of multispectral camera images lead to more efficient fertilization. This study aims to analyze the impact of the application of decomposers on the implementation of a multispectral camera image-based fertilizer recommendation system on soil physical properties, growth, and crop yield. This research was carried out from November 2021 to April 2022 at the experimental field in Sukamandijaya Village, Ciasem District, Subang Regency, West Java. This study was carried out with 2 treatments, namely land without the decomposers (P1) and with the decomposers treatment (P2) on rice fields of the Mekongga variety. The decomposer used was Petro Gladiator with dose 5 liters/ha (480 ml/plot or 56 ml/m²). Data analysis was carried out by unpaired T test at 5% level to determine the effect of decomposer application on soil physical properties as well as growth and crop yield. The results showed that the application of decomposers to fertilizer recommendation systems based on multispectral camera images can improve soil conditions including improvements in soil bulk density, soil particle density, total pore space, soil moisture content pF 1, 2, and 4.2, available pore water, then soil pH, available-P soil contents, potential-K soil content, as well as rice plant height.